Number 34 (December 1996) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1996)
(December 1996) - The Fishes of the Little River Drainage in Alabama. By Terri L. Ballard and J. Malcolm Pierson, 6pp., plus News Notes.
Keywords: fishes; little river drainage; alabama